2016
DOI: 10.1038/srep25440
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of aerobic exercise promote learning

Abstract: The benefits that physical exercise confers on cardiovascular health are well known, whereas the notion that physical exercise can also improve cognitive performance has only recently begun to be explored and has thus far yielded only controversial results. In the present study, we used a sample of young male subjects to test the effects that a single bout of aerobic exercise has on learning. Two tasks were run: the first was an orientation discrimination task involving the primary visual cortex, and the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 46 publications
(60 reference statements)
1
50
0
6
Order By: Relevance
“…Therefore, steps to expand the capacity of the adult brain for plasticity are of great interest because of the relevance to recovery from CNS disease and injury and for maintaining cognitive ability well into the last days of life. Previous studies have increased adult plasticity by various invasive and noninvasive manipulations such as environmental enrichment (Greifzu et al, 2014), antidepressant treatment (Maya Vetencourt et al, 2008), inhibitory neuron transplant, (Southwell et al, 2010), and others (for review, see Espinosa and Stryker, 2012). We have shown that exposure to high-contrast visual stimuli during locomotion improved recovery of visual cortical responsiveness from amblyopia (Kaneko and Stryker 2014) and enhanced the plasticity induced in adult cortex by monocular deprivation (Fu et al, 2015).…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, steps to expand the capacity of the adult brain for plasticity are of great interest because of the relevance to recovery from CNS disease and injury and for maintaining cognitive ability well into the last days of life. Previous studies have increased adult plasticity by various invasive and noninvasive manipulations such as environmental enrichment (Greifzu et al, 2014), antidepressant treatment (Maya Vetencourt et al, 2008), inhibitory neuron transplant, (Southwell et al, 2010), and others (for review, see Espinosa and Stryker, 2012). We have shown that exposure to high-contrast visual stimuli during locomotion improved recovery of visual cortical responsiveness from amblyopia (Kaneko and Stryker 2014) and enhanced the plasticity induced in adult cortex by monocular deprivation (Fu et al, 2015).…”
Section: Introductionmentioning
confidence: 67%
“…Also, it is unclear whether the benefits in performance observed are due to VR itself or purely due to exercise. There are well-documented effects of cardiovascular exercise upon cognition, thought to occur via upregulation of plasticity related proteins such as BDNF 30,31 . In order to determine whether VR accounts for any of this effect, a group of TBI survivors subjected to a non-VR exercise intervention is required.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…It has been shown that a beneficial effect of acute aerobic exercise in young human volunteers (improvement on an orientation discrimination task after 30 min on a stationary bicycle) can last at least 30 min after stopping the exercise (Perini et al, 2016). To test whether locomotor activity confers such benefit in mice, we allowed animals to run for 1 hr while viewing a grey screen and then returned them to the home cage and exposed them to a high contrast visual stimulus immediately thereafter.…”
Section: Locomotion Is Required For Response Enhancementmentioning
confidence: 99%